Peer effect of corporate R&D innovation from the perspective of uncertainty - Liu, Dayong; Cai, Yunpeng (Journal of Business Economics and Management, 2023)
Based on external uncertainty environment and R&D innovation wave background, this paper explores the impact of information noise caused by economic policy uncertainty and the peer effect on corporate R&D innovation activities, using the multiple regression method and the quarterly data of listed Chinese companies from 2010 to 2020, the influencing mechanism and boundary condition of economic policy uncertainty on the peer effect of corporate R&D were analyzed. Results show that there is a significant peer effect at the industry level in the R&D innovation behavior of corporates, with said effect and the uncertainty of economic policies both significantly stimulate the R&D innovation activities of corporates. The imitation learning path of peer effect is obviously targeted, and corporates in the same industry prioritize corporates with comparative advantages in the industry. Economic policy uncertainty and peer effect also present a certain selection effect on corporate R&D innovation, possibly further enabling corporates with better operating conditions to gain greater market share and gradually eliminate corporates with low R&D innovation ability. The conclusions help decision makers use the peer effect to implement incentive policies and optimize management.